PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH PADA BANK SULTRA CABANG PUNGGALUKU - Azis Muthalib, Dzulfikri; Masse, Ambo; Conny, Conny; Haprisia, Haprisia (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine and explain the effect of service quality dimensions on customer satisfaction at Bank Sultra Punggaluku Branch. The population is all customers. The sample was 99 customers. The analysis tool is multiple linear regression. The results show that: (1) Simultaneously there is a positive and significant influence of service quality dimension variables on customer satisfaction. (2) Tangible variables have a positive but insignificant effect on customer satisfaction. (3) The reliability variable has a positive and significant effect on customer satisfaction. The better the reliability, the higher the customer satisfaction (4) The responsiveness variable has a positive but insignificant effect on customer satisfaction. (5) Assurance variable has a positive and significant effect on customer satisfaction at Bank Sultra Punggaluku Branch. The better the assurance, the higher the customer satisfaction. (6) The empathy variable has a positive and significant effect on customer satisfaction. The better the empathy, the higher the customer satisfaction.